Study about Participation of Women in Dairy Farm Management Practices in Krishna District of Andhra Pradesh, India - Anitha, A. (Current Topics in Agricultural Sciences Vol. 2, 2021)
Women play a major role in dairy farm activities in India. They do most of the work in Animal Husbandry, yet remain as invisible workers. The present study is conducted to document their contribution to dairy farming. The participation of rural women in dairy farm activities is studied in Krishna district of Andhra Pradesh. A total of 225 farm women were selected based on their land holding capacity. The study revealed that women from small farmer category had more participation in taking animals for pregnancy diagnosis (81.33%) and post calving care (77.33%). Women under landless category were more involved in regularly taking animals for grazing (45.33%), green fodder collection and feeding (68%) and feeding animals with concentrates (88%). Feeding of animals with dry fodder regularly was more in small women dairy farmer category (89.33%) and landless (86.66%) than that in medium (56%) farm women category. Cleaning of animal sheds regularly was high in landless (76%) and small (69.33%) farm women than in medium (44%) farm women. Majority of women under landless category were regularly using disinfectants for cleaning of animal sheds (49.33%). Regular involvement in disposing of dung and composting of dung is high in women under landless (69.33%) and small (65.33%) farm women categories. Women under small (76%) and landless (73.33%) farmer category were regularly taking care of sick animals. More number of medium (9.33%) women dairy farmers were regularly involved in purchase of animals compared to landless (5.33%) and small (1.33%) farm women.